"Do you think your main partner has other sex partners?" A simple question provides insight into sexual risk in Jamaica. (January 2015) - Weir, Sharon S; Figueroa, J Peter; Byfield, Lovette L; Scott, Marion A; Hobbs, Marcia M; Edwards, Jessie E; Duncan, Jacqueline P
To estimate the association between a simple measure of sexual partner concurrency and sexually transmitted infection (STI) we conducted a cross-sectional population-based household survey ( n  = 1795) and targeted surveys of people at venues where people meet sexual partners ( n  = 1580) to ask about sexual behaviour. Persons interviewed at venues were tested for HIV, gonorrhoea, chlamydia, and trichomoniasis. We compared the association between STI and reporting a partner had other partners. More women than men reported their main partner had other partners. Thirteen percent of all women in the population-based survey and 14.4% in the targeted survey reported having one partner in the past 12 months and that partner had additional partners. STI prevalence was significantly associated with reporting a partner had other partners (36.8% vs. 30.2%; prevalence ratio [PR] 1.2; 95% confidence interval [CI] 1.1, 1.4). Construction of complete sexual networks is costly and not routinely feasible. We recommend adding a question to cross-sectional surveys used to monitor sexual behaviour about whether the respondent believes his or her partner has other sexual partners. Although subject to bias, the question was useful in Jamaica to identify a group of women with only one sexual partner at increased risk of infection.